Transatlantic Body Politics of the Spanish Civil War: Decoloniality and the Poetics of Internationalism - Jackson, Holly (Revista Canadiense de Estudios Hispánicos, 2023)
This article explores the poetics of internationalism in the Spanish Civil War, focusing on representations of the body in Spanish-language poetry. I contrast prevailing tropes of the body as an abstract figure for internationalism with the representation, in poems by Nicolás Guillén and Enrique Gil Gilbert, of specific bodies that nuance internationalism. These poems foreground the bodies of Black and Indigenous lyric subjects who summon antifascist Spain via their embodiment. They offer a “body politics,” which I define as the advancement of political theory through representation of a speaker’s geopolitically situated and embodied self, that heralds expressions of antifascism and international solidarity today.